SOCIAL PUBLICITY IN NUTRITION INCREASES THE SALAD CONSUMPTION OF USERS OF A UNIVERSITY RESTAURANT - Cândido, Flávia Galvão; Rocha, Daniela Mayumi Usuda Prado; Lopes, Lílian Lelis; Duarte, Maria Sônia Lopes (Journal of Health Care, 2015)
Introduction: Proper consumption of vegetables is important to maintain a good nutritional status andprevent chronic non-communicable diseases. Objective: Evaluating the impact of a social publicity onnutrition increasing salad consumption and acceptance from users of a university restaurant. Materialsand methods: This is an interventional study with a test-control representative sampling (n=1518,11.40%), in which it were elaborated nine banners with strong visual appeal and objective nutritionalinformation. The intervention consisted in the exhibition of banners during lunch in four non-consecutivedays in the test group. The salad portions were standardized before the intervention, and evaluatorsregistered the leftover-ingestion of the users who return their trays early at regular intervals of time inthe test and control groups. The analysis of results was made through the conversion of individual valuesfor total amounts of leftover-ingestion and consumption. The z-test (SigmaPlot software, version 11.0)was adopted to determine differences between treatments (P
Keywords: Vegetables; food services; food publicity; collective feeding; food and nutrition education.